Steroid responzívna encefalopatia asociovaná s autoimunitnou tyreoiditídou ako príčina akútnej encefalopatie - Maretta, Milan; Lacková, Alexandra; Wagnerová, Hedviga; Feketeová, Eva; Gdovinová, Zuzana (Vnitrni lekarstvi, 2023)
Steroid-responsive encephalopathy associated with autoimmune thyroiditis (SREAT), known as Hashimoto's encephalopathy (HE), represents a heterogeneous group of neurological and neuropsychiatric symptoms associated with a presence of antithyroid antibodies in case of other causes of encephalopathy were excluded. Clinical symptoms most commonly includes acute onset of encephalopathy, behaviour changes and cognitive dysfunction, epileptic seizures as well as cerebellar and extrapyramidal symptoms. Corticoids provides rapid and sustained therapeutic benefit in most patients and only a few patients require other immunosuppressive therapy such as plasmapheresis, intravenous immunoglobulins, or others. We present the cases of two patients with acute onset of encephalopathy, status epilepticus based on SREAT, with rapid improvement after steroid treatment.
Keywords: Brain Diseases; Steroid therapy; Hashimotova nemoc; Encephalitis; Steroids; status epilepticus; Hashimoto Disease; encefalitida; steroidy; lidé; Thyroiditis, Autoimmune; nemoci mozku; autoimunitní tyreoiditida; Humans; SREAT; corticoids